Cefotaxime Combination Antibacterial Activities And 10 Of Drug Plant Extract Bacteria Escherichia Coli Resistant And Methicillin Resistant Staphylococcus aureus ( MRSA ) - Arifin, Ary Isnaini; , Ratna Yuliani, M. Biotech. St (2016)
Resistance causes a decrease in antibacterial efficacy on antibiotics. Escherichia coli has been resistant to cefotaxime with percentage of 90.16% whereas Staphylococcus aureus resistant to cefotaxime with percentage of 82.69%. One effort that can be done to overcome the resistance is to combine antibiotics and plant extract. The purpose of this research were to investigate the antibacterial activity of the combination of cefotaxime and 10 plant extracts against E. coli and Methicillin Resistant Stapylococcus aureus (MRSA) and marker in extract that has the highest antibacterial activity. The extraction was done by maceration method. Antibacterial activity of extract against bacteria and combination of antibiotics with extract were perfomed with Kirby Bauer method. DMSO or ethanol was used as solvent control while the antibiotic control was cefotaxime. Thin Layer Chromatography (TLC) was done using mobile phase of toluene: ethyl acetate: methanol: formic acid (4:6:1:0,5) and silica gel GF254 nm as stationary phase. The results was observated under visible, UV 254 nm and UV 366 nm light. The result showed that plant extract did not enchance antibacterial activity of cefotaxime against E. coli and antibacterial activity againt MRSA increased when cefotaxime combined with galangal, garlic, and papaya leaf extract. Antibiotic activity test showed that extract of sappanwood produced the biggest inhibition zone against E. coli and MRSA. The results of the TLC showed that marker compound in sappanwood extract is brazillin.